Two-dimensional mesoporous nanosheet compound as well as preparation method and application thereof
Through the method of amphiphilic block copolymer micelle template and dopamine polymerization, a two-dimensional mesoporous nanosheet composite with spherical mesoporous structure was successfully prepared, which solved the problem of irregular mesoporous structure in the prior art and significantly improved the specific surface area and reactivity of the material.
Patent Information
- Application Number
- CN202510034922.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The prior art is difficult to synthesize two-dimensional mesoporous nanosheet composites with spherical mesoporous structures, which limits its performance in practical applications.
An amphiphilic block copolymer micelle was used as a template, and a two-dimensional mesoporous nanosheet composite with a spherical mesoporous structure was prepared by thermodynamic control and sonication, combined with oil bath stirring reaction and dopamine polymerization.
The prepared two-dimensional mesoporous nanosheet complex has a rich and special spherical mesoporous structure, which significantly improves its specific surface area and chemical reactive sites, providing better material transport channels and fast mass transfer power.
Smart Images

Figure CN119591108A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and more specifically, to a two-dimensional mesoporous nanosheet composite and a preparation method and application thereof. Background Art
[0002] As a new type of two-dimensional layered material, MXene material is mainly composed of transition metal carbides, nitrides, and carbonitrides, which lays the foundation for its unique properties, such as high conductivity, high mechanical strength, high chemically active surface, and low cost. Therefore, it has attracted widespread attention for its mechanical, thermal, electrical, magnetic, and optical properties. However, due to the van der Waals force and hydrogen bonds between MXene nanosheets and the metal atoms exposed on the surface, it is very easy to be oxidized and stacked. Introducing mesoporous structure on the basis of two-dimensional materials can not only improve its own defects but also further increase the rich active sites of nanomaterials and accelerate mass transfer / electron transfer, greatly improve the kinetics of the reaction, and further increase the zinc ion energy storage performance.
[0003] Most of the two-dimensional MXene mesoporous nanosheets prepared by the traditional template-free method and hard template method have fewer mesopores, and the pore size or arrangement is extremely irregular, which usually limits their practical application. Among them, the document "Stabilizing atomicCo on 2D ordered mesoporous carbon sandwiched MXene for peroxymonosulfateactivation: Enhanced performance and electron-transfer mechanism" discloses a soft template method using amphiphilic surfactant micelles as templates. Although it can synthesize ideal two-dimensional mesoporous nanosheets with the advantages of multiple mesopores, pore size and regular arrangement, the nanosheets obtained by this method usually have annular mesopores, resulting in ultra-long material transmission channels and extremely low mass transfer power, which limits its practical application. So far, the technology for synthesizing two-dimensional mesoporous nanosheets with spherical mesopores has not been reported. Therefore, developing a method for a two-dimensional mesoporous nanosheet composite constructed by spherical mesoporous elements is a synthetic hotspot and difficulty in this technical field. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a two-dimensional mesoporous nanosheet composite and a preparation method and application thereof, wherein the composite has a rich and special spherical mesoporous structure, which greatly improves the specific surface area of the two-dimensional mesoporous nanosheet composite, increases the active sites of chemical reactions, can provide better material transmission channels, and has rapid mass transfer power.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a two-dimensional mesoporous nanosheet composite, comprising the following steps: (1) using amphiphilic block copolymer micelles as basic templates, dissolving them in a solvent to obtain a block copolymer solution with a concentration of 0.1-40 mg / mL, and then preparing a single micelle solution by a thermodynamic control method; (2) The single micelle solution in step (1) is mixed with a single-layer MXene alcohol dispersion having a concentration of 2-5 mg / mL and subjected to ultrasonic treatment, and then an ammonia solution is added for oil bath stirring reaction. After the oil bath stirring reaction, the mixture is centrifuged, washed with water, and washed with anhydrous ethanol in sequence, and then redispersed in anhydrous ethanol to obtain a MXene@micelle single micelle superstructure alcohol solution having a concentration of 2-5 mg / mL; wherein the volume ratio of the single micelle solution, the single-layer MXene alcohol dispersion, and the ammonia solution is 3-6:1:0.025-0.03; (3) adding deionized water and bis(2-hydroxyethylaminotrimethylolmethane) buffer to the MXene@micelle single micelle superstructure alcohol solution in step (2), and performing ultrasonic treatment to make it evenly dispersed; then adding polydopamine, stirring and reacting at room temperature to obtain a polydopamine-wrapped MXene@micelle single micelle complex; wherein the mass ratio of the MXene@micelle single micelle superstructure alcohol solution, the deionized water, the bis(2-hydroxyethylaminotrimethylolmethane) buffer and the polydopamine is 1:1-5:0.006-1:0.001-1; (4) The MXene@micelle single micelle complex in step (3) is centrifuged, washed, and dried in sequence, and then calcined under a nitrogen atmosphere to obtain a two-dimensional mesoporous nanosheet complex constructed by spherical mesoporous elements.
[0006] Furthermore, the block copolymer in step (1) is one or more of polystyrene-polytetravinylpyridine-polyethylene oxide, polystyrene-polyacrylic acid-polyethylene oxide, and polystyrene-polyethylene oxide.
[0007] Furthermore, the solvent in step (1) is one or more of acetic acid, ethanol, water, DMF or a mixture of DMF and water.
[0008] Furthermore, in step (1), the thermodynamically controlled temperature is 20-110° C., and the time is controlled to be 0.5-10 h.
[0009] Furthermore, in step (2), the reaction temperature of the oil bath stirring reaction is 20-60°C, the stirring speed is 500-1000 rpm, the reaction time is 1-24 h, the centrifugal speed is 8000-15000 rpm, the water washing is 3-6 times, and the anhydrous ethanol washing is 3-6 times.
[0010] Furthermore, in the step (3), the stirring speed at room temperature is 500-800 rpm, and the reaction time is 1-100 h. Furthermore, in step (4), the centrifugal speed is 8000-15000 rpm; the washing conditions are: 95% ethanol solution is used for 3-6 washes; the drying conditions are: the drying temperature is 20-60 °C, and the drying time is 2-24 h.
[0011] Furthermore, in step (4), the roasting is divided into two stages, the roasting temperature of the first stage is 350-400°C, and the roasting time is 1-10 h; the roasting temperature of the second stage is 800-1000°C, and the roasting time is 1-10 h.
[0012] The present invention also provides the following technical solution: a two-dimensional mesoporous nanosheet composite, wherein a single layer of uniform spherical mesoporous structures are regularly arranged on both sides of the MXene nanosheet, and the pore size of the spherical mesopores is 22-46 nm; the specific surface area of the two-dimensional mesoporous nanosheet composite is 387-156 m 2 / g.
[0013] On the other hand, the present invention provides the following technical solution: application of a two-dimensional mesoporous nanosheet composite in a battery, wherein the two-dimensional mesoporous nanosheet composite is used as a positive electrode, a zinc sheet is used as a negative electrode, and an aqueous zinc salt electrolyte is used to assemble an aqueous zinc ion battery.
[0014] The advantages of the present invention are: 1. The present invention discloses a two-dimensional mesoporous nanosheet composite and a preparation method thereof. The two-dimensional mesoporous nanosheet composite is synthesized by a stable single micelle-assisted interface assembly method; that is, the surface of the MXene nanosheet is negatively charged, and its zeta potential is measured to be -11.24mV. The single micelle shows a positive charge with a zeta potential of 11.08 mV. Due to electrostatic attraction, the positively charged single micelle can be tightly anchored on the surface of the negatively charged MXene to form a closed @micelle-MXene-@micelle layered superstructure. Secondly, the polymerization of dopamine can be carried out not only on the single micelle, but also on the surface of the MXene nanosheet. This is due to the coexistence of hydrogen bonds between the PEO end and the −OH group of the PS-PVP-PEO single micelle and the -OH and -F end groups of the MXene nanosheet. The prepared two-dimensional mesoporous nanosheet composite has a rich and special spherical mesoporous structure, which greatly improves the specific surface area of the two-dimensional mesoporous nanosheet composite, increases the active sites of chemical reactions, can provide better material transmission channels, and has rapid mass transfer power.
[0015] 2. The present invention discloses an application of a two-dimensional mesoporous nanosheet composite, wherein the two-dimensional mesoporous nanosheet composite is used as the positive electrode, the zinc sheet is used as the negative electrode, and an aqueous zinc salt electrolyte is used to assemble an aqueous zinc ion battery, which has a higher discharge specific capacity and relatively stable long cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a scanning electron microscope image of the two-dimensional mesoporous nanosheet composite prepared in Example 1.
[0017] Figure 2 This is the elemental mapping of the two-dimensional mesoporous nanosheet composite prepared in Example 1.
[0018] Figure 3 This is a transmission electron microscopy image of the two-dimensional mesoporous nanosheet composite prepared in Example 1.
[0019] Figure 4 This is a transmission electron microscopy image of the two-dimensional mesoporous nanosheet composite prepared in Example 2.
[0020] Figure 5 This is a transmission electron microscopy image of the two-dimensional mesoporous nanosheet composite prepared in Example 3.
[0021] Figure 6 This is a transmission electron microscopy image of the two-dimensional mesoporous nanosheet composite prepared in Example 4.
[0022] Figure 7 This is a transmission electron microscopy image of the two-dimensional mesoporous nanosheet composite prepared in Example 5.
[0023] Figure 8The figure is a comparison chart of the specific capacity of the batteries assembled in Examples 1-5 and Comparative Example 1.
[0024] Fig. 9 This is a comparison chart of the long cycle of the batteries assembled in Examples 1-5 and Comparative Example 1. DETAILED DESCRIPTION
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0026] It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs.
[0027] In the present invention, unless otherwise specified, the directions used, such as "up" and "down", usually refer to the directions shown in the drawings, or to the vertical, perpendicular or gravity directions; similarly, for ease of understanding and description, "left" and "right" usually refer to the left and right shown in the drawings; "inside" and "outside" refer to the inside and outside relative to the outline of each component itself, but the above-mentioned directions are not used to limit the present invention.
[0028] Example 1: A method for preparing a two-dimensional mesoporous nanosheet composite, comprising the following steps: (1) 80 mg of amphiphilic block copolymer polystyrene-polytetravinylpyridine-polyethylene oxide (PS 106 -PVP 47 -PEO 113 ) micelles as the basic template, dissolved in 20 mL of acetic acid solution to obtain a block copolymer solution with a concentration of 20 mg / mL, kept at 110 ° C for 3 hours, then cooled to 25 ° C, and then placed in a dialysis bag for dialysis to obtain PS 106 -PV P47 -PEO 113 Monomicellar deionized water solution; (2) 1.5 mL of the single micelle deionized water solution in step (1) was added dropwise to 0.5 mL of a single-layer MXene alcohol dispersion with a concentration of 3.5 mg / mL, and ultrasonic treatment was performed. After ultrasonic treatment for 5 minutes, 100 μL of ammonia solution was added for oil bath stirring reaction, that is, stirring in a 40 °C oil bath for 12 h at a speed of 500 r / min. After the oil bath stirring reaction, centrifugation at a speed of 12000 rpm, water washing 5 times, and anhydrous ethanol washing 5 times were performed in sequence, and then it was redispersed in anhydrous ethanol to obtain a MXene@micelle single micelle superstructure alcohol solution with a concentration of 4 mg / mL; (3) Add 2 mL of deionized water to 2 mL of the MXene@micelle single micelle superstructure alcohol solution in step (2) to form a uniformly dispersed solution, then add 3 mg of di-2-hydroxyethylaminotrimethylolmethane buffer to the solution, and perform ultrasonic treatment to make it uniformly dispersed for 1 h; add 3 mg of polydopamine, and stir the reaction at room temperature at a speed of 600 rpm for 12 h to obtain a polydopamine-wrapped MXene@micelle single micelle complex; (4) The MXene@micelle single micelle complex in step (3) was centrifuged at 8000 r / min, then washed five times with 95% ethanol solution, dried at 50 °C for 18 h, and then calcined in a nitrogen atmosphere, that is, heat treated at 350 °C for 3 h to remove PS. 106 -PVP 47 -PEO 113 The single micelle soft template was then further increased to 800 °C for carbonization and calcined at this temperature for 3 h to obtain a two-dimensional mesoporous nanosheet composite constructed by spherical mesoporous elements.
[0029] The microstructure of the two-dimensional mesoporous nanosheet composite prepared in Example 1 was observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the element mapping of the two-dimensional mesoporous nanosheet composite prepared in Example 1 was measured. The results are as follows: Figure 1 , Figure 2 and Figure 3 As shown by Figure 1 , 2 As can be seen from Figures 3 and 4, the surface of the two-dimensional mesoporous nanosheet composite prepared in Example 1 has densely and regularly arranged superstructure protrusions, showing a rich and uniform spherical mesoporous structure, the pore size of the spherical mesopores is about 38 nm, and the thickness of the carbon layer is about 8 nm. The specific surface area of the composite of Example 1 is measured by a fully automatic gas adsorption instrument, and the specific surface area of the two-dimensional mesoporous nanosheet composite is 260 m 2 / g.
[0030] Example 2: The overall method is the same as that of Example 1, except that the amphiphilic block copolymer is PS 69 -PVP 42 -PEO 113 .
[0031] The microstructure of the two-dimensional mesoporous nanosheet composite prepared in Example 2 was observed by transmission electron microscopy (TEM). Figure 4 As shown by Figure 4It can be seen that the surface of the two-dimensional mesoporous nanosheet composite prepared in Example 2 has densely and regularly arranged superstructure protrusions, showing a rich and uniform spherical mesoporous structure, the pore size of the spherical mesopores is about 22 nm, and the thickness of the carbon layer is about 8 nm. The specific surface area of the composite of Example 2 is measured by a fully automatic gas adsorption instrument, and the specific surface area of the two-dimensional mesoporous nanosheet composite is 387 m 2 / g.
[0032] Example 3: The overall method is the same as that of Example 1, except that the amphiphilic block copolymer is PS 216 -PVP 56 -PEO 113 .
[0033] The microstructure of the two-dimensional mesoporous nanosheet composite prepared in Example 3 was observed by transmission electron microscopy (TEM). Figure 5 As shown by Figure 5 It can be seen that the surface of the two-dimensional mesoporous nanosheet composite prepared in Example 3 has densely and regularly arranged superstructure protrusions, showing a rich and uniform spherical mesoporous structure, the pore size of the spherical mesopores is about 46 nm, and the thickness of the carbon layer is about 8 nm. The specific surface area of the composite of Example 3 was measured by a fully automatic gas adsorption instrument, and the specific surface area of the two-dimensional mesoporous nanosheet composite was 156 m 2 / g.
[0034] Example 4: A method for preparing a two-dimensional mesoporous nanosheet composite, comprising the following steps: (1) 10 mg of amphiphilic block copolymer polystyrene-polytetravinylpyridine-polyethylene oxide (PS 106 -PVP 47 -PEO 113 ) micelles as the basic template, dissolved in 100 mL of acetic acid solution to obtain a block copolymer solution with a concentration of 0.1 mg / mL, kept at 20 °C for 0.3 hours, then cooled to 25 °C, and then placed in a dialysis bag for dialysis to obtain PS 106 -PV P47 -PEO 113 Monomicellar deionized water solution; (2) 3 mL of the single micelle deionized water solution in step (1) was added dropwise to 1 mL of a single-layer MXene alcohol dispersion with a concentration of 2 mg / mL, and ultrasonic treatment was performed. After ultrasonic treatment for 5 minutes, 0.025 μL of ammonia solution was added for oil bath stirring reaction, that is, stirring in a 20 °C oil bath for 1 h at a speed of 750 r / min. After the oil bath stirring reaction, centrifugation at a speed of 8000 rpm, washing with water 3 times, and washing with anhydrous ethanol 3 times were performed in sequence, and then redispersed in anhydrous ethanol to obtain a MXene@micelle single micelle superstructure alcohol solution with a concentration of 2 mg / mL; (3) Add 1 mL of deionized water to 1 mL of the MXene@micelle single micelle superstructure alcohol solution in step (2) to form a uniformly dispersed solution, then add 0.006 mg of bis-2-hydroxyethylaminotrimethylolmethane buffer to the solution, and perform ultrasonic treatment to make it uniformly dispersed for 1 h; add 6 mg of polydopamine, stir at room temperature at a speed of 800 rpm for 1 h to obtain a polydopamine-wrapped MXene@micelle single micelle complex; (4) The MXene@micelle single micelle complex in step (3) was centrifuged at 12000 r / min, then washed three times with 95% ethanol solution, dried at 20 °C for 2 h, and then calcined in a nitrogen atmosphere, that is, heat treated at 370 °C for 1 h to remove PS. 106 -PVP 47 -PEO 113 The single micelle soft template was then further increased to 900 °C for carbonization and calcined at this temperature for 1 h to obtain a two-dimensional mesoporous nanosheet composite constructed by spherical mesoporous elements.
[0035] The microstructure of the two-dimensional mesoporous nanosheet composite prepared in Example 4 was observed by transmission electron microscopy (TEM). Figure 6 As shown by Figure 6 It can be seen that the two-dimensional mesoporous nanosheet composite prepared in Example 4 exhibits a rich and uniform spherical mesoporous structure, the pore size of the spherical mesopores is about 38 nm, and the thickness of the carbon layer is about 20 nm. The specific surface area of the composite of Example 4 is measured by a fully automatic gas adsorption instrument, and the specific surface area of the two-dimensional mesoporous nanosheet composite is 256 m 2 / g.
[0036] Example 5: A method for preparing a two-dimensional mesoporous nanosheet composite, comprising the following steps: (1) 80 mg of amphiphilic block copolymer polystyrene-polytetravinylpyridine-polyethylene oxide (PS106 -PVP 47 -PEO 113 ) micelles were used as the basic template and dissolved in 2 mL of acetic acid solution to obtain a block copolymer solution with a concentration of 40 mg / mL. The solution was kept at 65 °C for 10 hours, then cooled to 25 °C, and then dialyzed into a dialysis bag to obtain PS 106 -PV P47 -PEO 113 Monomicellar deionized water solution; (2) 6 mL of the single micelle deionized water solution in step (1) was added dropwise to 1 mL of a single-layer MXene alcohol dispersion with a concentration of 5 mg / mL, and ultrasonic treatment was performed. After ultrasonic treatment for 5 minutes, 0.03 μL of ammonia solution was added for oil bath stirring reaction, that is, stirring in a 60 °C oil bath for 24 h at a speed of 1000 r / min. After the oil bath stirring reaction, centrifugation at a speed of 15000 rpm, washing with water 6 times, and washing with anhydrous ethanol 6 times were performed in sequence, and then redispersed in anhydrous ethanol to obtain a MXene@micelle single micelle superstructure alcohol solution with a concentration of 5 mg / mL; (3) Add 5 mL of deionized water to 1 mL of the MXene@micelle single micelle superstructure alcohol solution in step (2) to form a uniformly dispersed solution, then add 1 mg of di-2-hydroxyethylaminotrimethylolmethane buffer to the solution, and perform ultrasonic treatment to make it uniformly dispersed for 1 h; add 10 mg of polydopamine, and stir the reaction at room temperature at a speed of 500 rpm for 100 h to obtain a polydopamine-wrapped MXene@micelle single micelle complex; (4) The MXene@micelle single micelle complex in step (3) was centrifuged at 15000 r / min, then washed six times with 95% ethanol solution, dried at 60 °C for 24 h, and then calcined in a nitrogen atmosphere, that is, heat treated at 400 °C for 10 h to remove PS. 106 -PVP 47 -PEO 113 The single micelle soft template was then further increased to 1000 °C for carbonization and calcined at this temperature for 10 h to obtain a two-dimensional mesoporous nanosheet composite constructed by spherical mesoporous elements.
[0037] The microstructure of the two-dimensional mesoporous nanosheet composite prepared in Example 5 was observed by transmission electron microscopy (TEM). Figure 7 As shown by Figure 7It can be seen that the two-dimensional mesoporous nanosheet composite prepared in Example 5 exhibits a rich and uniform spherical mesoporous structure, the pore size of the spherical mesopores is about 38 nm, and the thickness of the carbon layer is about 30 nm. The specific surface area of the composite of Example 2 is measured by a fully automatic gas adsorption instrument, and the specific surface area of the two-dimensional mesoporous nanosheet composite is 265 m 2 / g.
[0038] Among them, the elementary templates of Examples 1-3 are different. As the length of PS in the template increases, the pore size of the spherical mesopores of the obtained two-dimensional mesoporous nanosheet composite becomes larger, among which the spherical mesopores of the two-dimensional mesoporous nanosheet composite prepared in Example 2 have the smallest pore size; the amount of polydopamine added in Examples 4-5 is increased compared with that in Example 1, which leads to an increase in the carbon layer thickness of the obtained two-dimensional mesoporous nanosheet composite with the increase in the amount of polydopamine added.
[0039] Preparation of battery: First, the two-dimensional mesoporous nanosheet composite prepared in Examples 1-5 was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1. Then, n-methyl-2-pyrrolidone solvent was added and stirred for 5 hours to obtain a slurry. Secondly, the obtained slurry was coated on a stainless steel foil as a positive electrode. Finally, the above positive electrode, zinc sheet negative electrode, electrolyte (2 M ZnSO 4 -7H 2 O) and glass microfiber separators were assembled into button cells (CR2025 type) for further testing process.
[0040] Comparative Example 1: First, the annular mesoporous nanosheets, conductive carbon black and polyvinylidene fluoride in the prior art were mixed in a mass ratio of 8:1:1. Then, n-methyl-2-pyrrolidone solvent was added and stirred for 5 hours to obtain a slurry. Secondly, the obtained slurry was coated on a stainless steel foil as a positive electrode. Finally, the above positive electrode, zinc sheet negative electrode, electrolyte (2 M ZnSO 4 -7H 2 O) and glass microfiber separators were assembled into button cells (CR2025 type) for further testing process.
[0041] Experiment: The aqueous zinc ion batteries assembled in Examples 1-5 and Comparative Example 1 were tested for charge and discharge, and the results are as follows: Figure 8 and Fig. 9 As shown by Figure 8 and 9 It can be seen that the battery prepared in Example 1 has a -1 158 mA hg -1 The high specific capacity and the -1When the capacity is maintained at 0.1 A g, the capacity retention rate is 83% after 5000 cycles. -1 176 mA hg -1 The high specific capacity and the -1 When the capacity is maintained at 0.1 A g, the capacity retention rate is still 85% after 5000 cycles; the battery prepared in Example 3 -1 130 mAh g -1 The high specific capacity and the -1 When the capacity is maintained at 0.1 A g, the capacity retention rate is still more than 82% after 5000 cycles; the battery prepared in Example 4 -1 100 mA hg -1 The high specific capacity and the -1 When the capacity is maintained at 0.1 A g, the capacity retention rate is still more than 81% after 5000 cycles; the battery prepared in Example 5 -1 105 mA hg -1 The high specific capacity and the -1 When the capacity is maintained at 0.1 A g, the capacity retention rate is still more than 84% after 5000 cycles; the battery prepared in Comparative Example 1 -1 80 mA hg -1 The specific capacity and the current density of 5 A g -1 When the battery is assembled with the materials prepared in Examples 1-5, its capacity retention rate is only 70% after 5000 cycles; therefore, the performance of the battery assembled with the materials prepared in Examples 1-5 is much higher than that of the battery prepared in Comparative Example 1, and the two-dimensional mesoporous nanosheet composite prepared in Example 2 has spherical mesopores with smaller pore size and higher specific surface area, which leads to more active sites for chemical reactions, can provide better material transport channels, and has fast mass transfer power. Therefore, the discharge specific capacity and long cycle performance of the battery assembled with the materials prepared in Example 2 are the best compared with those in other examples. Therefore, the two-dimensional mesoporous nanosheet composite prepared in the present invention has higher discharge specific capacity and more stable long cycle performance.
[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0043] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a two-dimensional mesoporous nanosheet composite, characterized in that: It includes the following steps: (1) using amphiphilic block copolymer micelles as basic templates, dissolving them in a solvent to obtain a block copolymer solution with a concentration of 0.1-40 mg / mL, and then preparing a single micelle solution by a thermodynamic control method; (2) The single micelle solution in step (1) is mixed with a single-layer MXene alcohol dispersion having a concentration of 2-5 mg / mL and subjected to ultrasonic treatment, and then an ammonia solution is added for oil bath stirring reaction. After the oil bath stirring reaction, the mixture is centrifuged, washed with water, and washed with anhydrous ethanol in sequence, and then redispersed in anhydrous ethanol to obtain a MXene@micelle single micelle superstructure alcohol solution having a concentration of 2-5 mg / mL; wherein the volume ratio of the single micelle solution, the single-layer MXene alcohol dispersion, and the ammonia solution is 3-6:1:0.025-0.03; (3) adding deionized water and bis(2-hydroxyethylaminotrimethylolmethane) buffer to the MXene@micelle single micelle superstructure alcohol solution in step (2), and performing ultrasonic treatment to make it evenly dispersed; then adding polydopamine, stirring and reacting at room temperature to obtain a polydopamine-wrapped MXene@micelle single micelle complex; wherein the mass ratio of the MXene@micelle single micelle superstructure alcohol solution, the deionized water, the bis(2-hydroxyethylaminotrimethylolmethane) buffer and the polydopamine is 1:1-5:0.006-1:0.001-1; (4) The MXene@micelle single micelle complex in step (3) is centrifuged, washed, and dried in sequence, and then calcined under a nitrogen atmosphere to obtain a two-dimensional mesoporous nanosheet complex constructed by spherical mesoporous elements.
2. The method for preparing a two-dimensional mesoporous nanosheet composite according to claim 1, characterized in that: The block copolymer in the step (1) is polystyrene-polytetravinylpyridine-polyethylene oxide.
3. The method for preparing a two-dimensional mesoporous nanosheet composite according to claim 1, characterized in that: The solvent in step (1) is one or more of acetic acid, ethanol, water, DMF or a mixture of DMF and water.
4. The method for preparing a two-dimensional mesoporous nanosheet composite according to claim 1, characterized in that: In the step (1), the thermodynamically controlled temperature is 20-110° C. and the time is controlled to be 0.5-10 h.
5. The method for preparing a two-dimensional mesoporous nanosheet composite according to claim 1, characterized in that: In the step (2), the reaction temperature of the oil bath stirring reaction is 20-60°C, the stirring speed is 500-1000 rpm, the reaction time is 1-24 h; the centrifugal speed is 8000-15000 rpm, the water washing is 3-6 times, and the anhydrous ethanol washing is 3-6 times.
6. The method for preparing a two-dimensional mesoporous nanosheet composite according to claim 1, characterized in that: In the step (3), the stirring speed at room temperature is 500-800 rpm, and the reaction time is 1-100 h.
7. The method for preparing a two-dimensional mesoporous nanosheet composite according to claim 1, characterized in that: In the step (4), the centrifugal speed is 8000-15000 rpm; the washing condition is to use 95% ethanol solution for 3-6 washes; the drying condition is to use a drying temperature of 20-60°C and a drying time of 2-24 h.
8. The method for preparing a two-dimensional mesoporous nanosheet composite according to claim 1, characterized in that: In the step (4), the roasting is divided into two stages. The roasting temperature in the first stage is 350-400°C and the roasting time is 1-10 h; the roasting temperature in the second stage is 800-1000°C and the roasting time is 1-10 h.
9. The two-dimensional mesoporous nanosheet composite prepared by the preparation method according to any one of claims 1 to 8, characterized in that: On both sides of the MXene nanosheet, a single layer of uniform spherical mesoporous structure is regularly arranged, and the pore size of the spherical mesopores is 22-46 nm. The specific surface area of the two-dimensional mesoporous nanosheet composite is 387-156 m 2 / g.
10. The use of the two-dimensional mesoporous nanosheet composite in a battery as claimed in claim 9, characterized in that: The two-dimensional mesoporous nanosheet composite is used as the positive electrode, the zinc sheet is used as the negative electrode, and an aqueous zinc salt electrolyte is used to assemble an aqueous zinc ion battery.
Citation Information
Patent Citations
Preparation method and application of two-dimensional mesoporous polyaniline / MoS2 composite nano material
CN107731569A
Two-dimensional nitrogen-doped carbon material with through mesoporous structure and preparation method thereof
CN108597911A
Preparation method of porous polydopamine nanoparticles with controllable morphology
CN110498946A
Preparation method and application of two-dimensional MXene / polydopamine composite desalination electrode material
CN113881040A
Raspberry-shaped mesoporous carbon sphere with high specific surface area and preparation method of raspberry-shaped mesoporous carbon sphere
CN117534058A
Cited By
Simple and rapid preparation method and application of two-dimensional in-plane mesoporous polydopamine nanosheet
CN120966082A
One-dimensional mesoporous bismuth oxide nanorod constructed based on spherical mesopores and preparation method thereof
CN122010174A